Las asignaciones presupuestarias y su incidencia en la gestión administrativa en el gobierno autónomo descentralizado municipal de quevedo, año 2024 - Mora Reinoso, Darwin Alexander (2025)
The present study on budget allocations in the Autonomous Municipality of Quevedo in 2024 examines the key relationship between budget allocations and the efficiency of administrative management. The main objectives include assessing the impact of these allocations on the quality of life of residents and identifying opportunities to optimize the use of public resources. The issue concerns the difficulties related to budget management, especially in the context of limited resources and increasing demands from citizens. The primary rationale for this research comes from the need to understand how the way funds are allocated influences the planning, implementation and evaluation of urban projects, which has direct consequences for the quality of public services. The methodology is based on qualitative and quantitative research, including interviews and analysis of budget documentation. This research identifies decision-making processes and their impact on project prioritization. It also addresses issues of transparency and accountability in budget management, analyzing the effectiveness of public